Bottlenose Dolphins and Antillean Manatees Respond to Small Multi-Rotor Unmanned Aerial Systems - Ramos, Eric A.; Maloney, Brigid; Magnasco, Marcelo O.; Reiss, Diana (Frontiers in Marine Science, 2018)
Unmanned aerial systems (UAS) are powerful tools for research and monitoring of wildlife. However, the effects of these systems on most marine mammals are largely unknown, preventing the establishment of guidelines that will minimize animal disturbance. In this study, we evaluated the behavioral responses of coastal bottlenose dolphins (Tursiops truncatus) and Antillean manatees (Trichechus manatus manatus) to small multi-rotor UAS flight. From 2015 to 2017, we piloted 211 flights using DJI quadcopters (Phantom II Vision +, 3 Professional and 4) to approach and follow animals over shallow-water habitats in Belize. The quadcopters were equipped with high-resolution cameras to observe dolphins during 138 of these flights, and manatees during 73 flights. Aerial video observations of animal behavior were coded and paired with flight data to determine whether animal activity and/or the UAS’s flight patterns caused behavioral changes in exposed animals. Dolphins responded to UAS flight at altitudes of 11–30 m, and responded primarily when they were alone or in small groups. Single dolphins and one pair responded to the UAS by orienting upward and turning towards the aircraft to observe it, before quickly returning to their pre-response activity. A higher number of manatees responded to the UAS, exhibiting strong disturbance in response to the aircraft from 6–104 m. Manatees changed their behavior by fleeing the area and sometimes this elicited the same response in nearby animals. If pursued post-response, manatees repeatedly responded to overhead flight by evading the aircraft’s path. These findings suggest that the invasiveness of UAS varies across individuals, species, and taxa. We conclude that careful exploratory research is needed to determine the impact of multi-rotor UAS flight on diverse species, and to develop best practices aimed at reducing the disturbance to wildlife that may result from their use.